Archives Management in the Publi Pengelolaan Arsip Divisi Humas dan Community Development PT Indonesia Power Suralaya Power Generation Unit Cilegon - Winanti, Alvina Cahya (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
The Public Relations and Community Development Division of PT Indonesia Power Suralaya PGU in carrying out their duties cannot be separated from the existence of documents that will later be archived for further use as evidence of the activities that the Public Relations and Comdev Division have carried out. The problems found in this study are the lack of coordination between employees, archive storage that is not well organized, and incomplete archives. This research was conducted aiming to find out how archive management is done. This study used a qualitative descriptive method using a purposive sampling technique. Then, in collecting research data, the authors used the methods of observation, participation, documentation and interviews. Based on the research conducted, it can be seen that archive management in the Division of Public Relations and Community Development at PT Indonesia Power Suralaya PGU, with the initial stage of planning, determines the storage period for archives. The next stage is to mobilize by archiving in the form of softcopy and hardcopy. Then, there is an organizing stage which is carried out by giving authority to employees in charge of data and documents. Finally, for the supervision stage, monitoring is carried out for all employees. From the results of the study it was concluded that the management carried out had gone through the stages of planning, actuating, organizing, and supervising as stated by Wardoyo regarding the focus of management.